1980
DOI: 10.1016/s0006-3495(80)85144-7
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear magnetic resonance analysis of water in natural and deuterated mouse muscle above and below freezing

Abstract: Measurements of absolute proton signal intensities, free induction decays, spin-spin relaxation times, and local fields in the rotating frame in natural and fully deuterated mouse muscle at five temperatures in the range 293-170 K are reported. The analysis is carried out at three time windows on the free induction decay. The contribution to the magnetization from protons on large molecules and water are analyzed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

1982
1982
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…The FID and T2 results in muscle agree with the published data (12,23,24). The SS-component, which was deduced indirectly a few years ago from measurements in fully deuterated muscle (24), is resolved in the present experiment in the natural muscle.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The FID and T2 results in muscle agree with the published data (12,23,24). The SS-component, which was deduced indirectly a few years ago from measurements in fully deuterated muscle (24), is resolved in the present experiment in the natural muscle.…”
Section: Resultssupporting
confidence: 90%
“…In these studies, the NMR relaxation measurements have been taken at only one time window on the free induction decay (FID). The resolution of the heterogenous spin distribution was improved if the relaxation measurements were taken at two time windows (23,24). A further improvement of the resolution of spin distributions in these complex systems was achieved by a two-dimensional (2D) NMR technique (38,39).…”
Section: Introductionmentioning
confidence: 99%
“…The values given by Kiricuta and Hazlewood (13, 1) correspond to the values for our T2, Component values. Careful measurements of a number of investigators on muscle from a variety of species have demonstrated that there exist three or more compartments (3, 14). These authors gave relaxation spin-spin times of water in the range from 30 to 500 ms.…”
Section: Discussionmentioning
confidence: 99%
“…Many investigators have examined the contributions of a variety of different environments to the NMR relaxation properties of water molecules in biological systems (32)(33)(34)(35). Although the mechanisms for alteration of the proton Tl and Tz relaxation times by pharmaceuticals may be complex, a few general conclusions may be drawn.…”
Section: Discusslohmentioning
confidence: 99%